2003
DOI: 10.1128/aac.47.4.1200-1206.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Injury and Resuscitation of Candida albicans after Amphotericin B Treatment

Abstract: Amphotericin B treatment was previously shown to inhibit Candida albicans reproduction and reduce the fluorescence of vitality-specific dyes without causing a corresponding increase in the fluorescence of the mortality-specific dyes bis-(1,3-dibutylbarbituric acid)trimethine oxonol and SYBR Green ⌱. In the present study, we have confirmed these results and have shown that the numbers of CFU are reduced by 99.9% by treatment with 0.5 g of amphotericin B per ml for 10 h at 35°C. This reduction was not due to fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…The low level of membrane disruption can be further demonstrated by the poor influx of PI. PI is most commonly used as an indicator for cell death or cells with compromised membrane because it is not taken up by cells with an intact plasma membrane, and thus, can only enter cells that have lost their membrane integrity (Jepras et al 1995;Comas and Vives-Rego 1997;Novo et al 2000;Amor et al 2002;Liao et al 2003). In our study, although the PI staining rates showed dose-and timedependent increases, the PI did not significantly enter cells until the time cultures were exposed to 20 mmol l )1 of ClO 2 for 5 min, during which 99AE99% of cells were inactivated (Figs 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…The low level of membrane disruption can be further demonstrated by the poor influx of PI. PI is most commonly used as an indicator for cell death or cells with compromised membrane because it is not taken up by cells with an intact plasma membrane, and thus, can only enter cells that have lost their membrane integrity (Jepras et al 1995;Comas and Vives-Rego 1997;Novo et al 2000;Amor et al 2002;Liao et al 2003). In our study, although the PI staining rates showed dose-and timedependent increases, the PI did not significantly enter cells until the time cultures were exposed to 20 mmol l )1 of ClO 2 for 5 min, during which 99AE99% of cells were inactivated (Figs 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…The exact reasons for this lower-than-expected response still remain unclear. Some authors do not associate response failure with target modification, as has been observed with other antifungal drugs (11), but with inappropriate concentrations of AMB at the infection site (12). In accordance with this hypothesis, cells exposed to amphotericin B may exhibit different physiological conditions which are related to drug concentration and exposure time (12).…”
mentioning
confidence: 57%
“…Some authors do not associate response failure with target modification, as has been observed with other antifungal drugs (11), but with inappropriate concentrations of AMB at the infection site (12). In accordance with this hypothesis, cells exposed to amphotericin B may exhibit different physiological conditions which are related to drug concentration and exposure time (12). In addition, studies of yeast apoptosis have revealed the occurrence of a programmed cell death or a cellular necrotic response depending on the AMB concentration (13,14).…”
mentioning
confidence: 69%
See 2 more Smart Citations